The Role of Internet of Things (IoT) in Enhancing Asset Management and Operational Efficiency - Zein, Afrizal; Karimah, Mufidah (JAKI : Jurnal Akuntansi, 2025)
The advancement of Internet of Things (IoT) technology has brought significant changes in enhancing asset management and operational efficiency across various organizations. This study aims to explore how IoT implementation can improve asset management through real-time monitoring, automation, and better data integration. The research employs a qualitative approach using a case study of an institution that has adopted IoT technology. Data were collected through in-depth interviews with stakeholders, direct observations, and a comprehensive literature review from reliable online sources such as Google Scholar. The data were analyzed descriptively to identify the impact of IoT on asset management processes and operational efficiency. The findings reveal that IoT enables organizations to reduce manual errors, optimize asset utilization, and significantly lower operational costs. Moreover, IoT accelerates responses to operational issues and enhances transparency in asset management. The study also highlights challenges in implementation, including the need for system integration and data security concerns. These findings contribute valuable insights into the role of IoT in the digital transformation of asset management and operations and serve as a reference for practitioners and academics in developing effective IoT deployment strategies.